Treatment of Infectious Complications of Acute Pancreatitis in a Specialized Department of Purulent and Septic Surgery - M. I. Prudkov; B. B. Gafurov; F. V. Galimzyanov (Неотложная медицинская помощь, 2020)
AIM OF STUDY. To show the implementation of routing, results and methods of surgical treatment of patients with infectious complications of acute pancreatitis in specialized department of septic surgery of a regional hospital.MATERIAL AND METHODS. After managing pancreatogenic shock and stabilization of the patient’s condition, the emergency medical teams or the territorial center of disaster medicine transferred the patients to the regional septic center (Department of Purulent and Septic Surgery of Sverdlovsk Regional Clinical Hospital No. 1). Over the past 5 years, 422 patients with acute pancreatitis of severe and moderate severity were transferred: 62 patients with peripancreatic infiltrates and signs of infection, but without a liquid component; 76 patients with pancreatogenic abscesses, 284 patients with non-localized variants of septic sequestration.RESULTS. Infected peripancreatic infiltrates complicated by sepsis without a liquid component. An attempt of surgical separation and drainage was made in 19 patients out of 62. Nine patients (47.4%) died. Subsequently, the remaining 43 patients were treated conservatively and 11 (25.5%) patients died. Pancreatogenic abscesses (delimited septic sequestration). All 76 patients were operated with the use of minimally invasive technologies (navigation punctures, navigation puncture drainage, drainage and sequestration from the mini-access). There were no deaths. Non-localized pancreatogenic septic sequestration (pancreatogenic phlegmon). Suppuration areas within one quadrant (S1 or D1) occurred in 120 patients. All of them were simultaneously drained from 1–2 incisions of 3–5 cm, 16 patients died (13.3 %), another 164 patients had more common variants of lesions (2–5 quadrants), including central localization (C), 64 patients of them were operated simultaneously, 18 patients died (28.1%). Another 100 patients were operated using stage-by-stage drainage tactics, and 21 patients died (21%).CONCLUSION. 1. The modern treatment of patients with purulent-septic forms of pacreatogenic lesions of retroperitoneal cellular spaces requires effective resuscitation support, verification of the form of the inflammatory process, high-precision visualization of foci of suppuration and the use of a wide range of modern minimally invasive surgical technologies.2. The development and implementation of regional programs for routing patients with infectious complications of acute pancreatitis and providing them with staged medical care can improve the results of surgical treatment and reduce mortality from 28.1% to 19.3%.Authors declare lack of the conflicts of interests.